Examining the relationship among constraints, facilitators and ski participation in the host city of the 2022 Winter Olympics - Yang, Y.; Macintosh, E.; Xing, X. (International Journal of Sports Marketing & Sponsorship, 2024)
Purpose The study`s purpose is to investigate the constraints and facilitators influencing skiing participation in Beijing. This research includes three segments based on the frequency of skiing participation (i.e. non-, low-frequency-, and high-frequency skiers). By doing so, the study offers an enhanced understanding of the Chinese skiing market and unveils insights assisting industry professionals to effectively address their customers' diverse needs and expectations.